Fracture characteristics of a cement concrete pavement plate considering subgrade modulus decay based on a meshless finite block method - Wei, Hui; Zhou, Yu; Huang, Wang; Wen, Pihua; Li, Jue (Frontiers in Materials, 2023)
The decrease in the subgrade modulus immersed in rainwater can significantly increase the fracture risk of a cement concrete pavement plate. The aim of this study was to develop a meshless finite block method (MFBM) to reveal the failure mechanism of a cement concrete pavement due to the weakening of the subgrade modulus. A normal distribution function was adopted in this study to represent the distribution of the subgrade modulus at the bottom of the cement concrete pavement plate. The settlement results show that the progressive softening model of soil subgrade is more suitable to represent subgrade modulus decay. The maximum stress of the cement concrete pavement mainly concentrates at 1.05–1.15 m of the plate edge. The weak fracture position is influenced by the subgrade modulus reduction, the size of the immersion range, and the pavement and subgrade thickness. When improving the subgrade modulus, adding plate thickness appropriately can effectively control the cracking of the cement concrete pavement. Compared with the finite element model, it is proved that the proposed MFBM has an advantage in the solution of pavement fracture with high accuracy and less computation time. In addition, findings in this study may provide evidence for understanding the effect of the subgrade modulus on the durable pavement design.